Zeitschrift für Wettbewerbsrecht : Journal of Competition Law (RWS-Verlag, 2003)
The ZWeR is a forum for in-depth research analysis on fundamental, current and practical themes of general and sector-specific anti-trust law, contract-awarding law and state aid controlling law. With international and economic correlations, the ZWeR publishes articles in both German and English, in-depth discussions of important court rulings and provides an overview of the current state of the discussion and the literature. The ZWeR turns to legal minds who work in anti-trust, competition and contract-awarding law as well as correspondingly-oriented economists from research and practice at companies, in the courts, government agencies, universities, professional associations and among attorneys.